Speaking Trade, Aiming Beyond: Israel’s Economic Relations with France and Britain before 1956 - Zouplna, Jan (Oriente moderno, 2020)
Abstract Israel’s relationship with the West during the first half of the 1950s was not a walk in the park. Economic relations fitted into this general picture. Both Britain and France were sceptical as far as Israel’s potential was concerned. Their early prognoses tended to be quite gloomy. Simultaneously, economic relations provided a convenient communication channel at a time when overt association with the Jewish state was not desirable. The progress in Franco-Israeli economic ties during the years 1953-1955 illustrates this ambivalence in full. While prudence remained, the increase in bilateral trade managed to warrant the military supplies. Britain, constituting a traditional market, surpassed France as a trading partner. Given British political aloofness, the instrument of trade served primarily its immediate economic purpose. Based on archival sources gathered in all of the three countries, the paper traces the interplay of trade and diplomacy in the early years of Israel’s foreign relations.